The Effect of Education on Happiness, Self-Acceptance, and Family Harmony (Empirical Evidence from Indonesia) - Hanifah Umi Haryati (The Journal of Indonesia Sustainable Development Planning, 2023)
Education plays a crucial role in determining the quality of life through economic returns and subjective well-being. However, almost no previous research has examined how education affects subjective well-being indicators beyond happiness. To address this gap, this study used Ordinary Least Squares and the Ordered Probit technique to investigate the effect of education on happiness, self-acceptance, and family harmony. Using the recent microdata from Statistics Indonesia in 2021 the empirical results reveal that education positively affects happiness, self-acceptance, and family harmony. The effect of education remained statistically significant even after incorporating socioeconomic and individual characteristics such as income, gender, age, marital status, home ownership, household size, area classification, health status, and leisure time. The result of this study highlights that individuals with higher levels of education reported higher happiness, greater self-acceptance, and higher satisfaction with family harmony than those with lower levels of education. Although more than half of the magnitude of the education effect decreases after incorporating socioeconomic and individual characteristics variables, the direct effect of education remained significant on happiness, self-acceptance, and family harmony.